Energy efficiency measures at hungarian ice rinks - Márton, Laura; Ráthonyi-Ódor, Kinga (Acta Carolus Robertus, 2024)
Since the 2000s, there has been a gradual increase in the number of studies examining the responsible behavior of sports organizations and companies in the sports sector. One of the most important topics today is the energy crisis, and therefore the introduction of possible energy efficiency measures. The purpose of this study is to present the energy efficiency measures implemented at the ice rinks in Hungary, as well as future environmental protection plans. To answer my research questions, I used comparative analysis based on secondary data sources and conducted expert interviews with professionals from 3 Hungarian ice hockey clubs about the innovations they have introduced at their rinks and their short- and long-term environmental goals. Finally, I examined the ’MJSZ ice rink energy audit summary’ prepared by the Hungarian Ice Hockey Federation. My research gave me a more accurate picture of the measures taken at the rinks. By describing the environmental protection and energy efficiency measures revealed in the study, I can present good practises that can serve as a guiding example for the domestic sports sector.